2003
DOI: 10.1053/jhep.2003.50107
|View full text |Cite
|
Sign up to set email alerts
|

Extending Combination Therapy With Peginterferon Alfa–2B Plus Ribavirin for Genotype 1 Chronic Hepatitis C Late Responders: A Report of 9 Cases

Abstract: The large number of chronic hepatitis C patients infected by genotype 1 constitutes an important therapeutic challenge because they are the most resistant to combination therapy with interferon alfa and ribavirin. [1][2][3] In these patients, the sustained virologic response to peginterferon and ribavirin for 48 weeks is around 42%. 3,4 It has been shown that one important factor of sustained virologic response (SVR) is rapid hepatitis C virus (HCV)-RNA clearance, ranging from 75% for those patients who cleare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 8 publications
0
32
0
3
Order By: Relevance
“…Seventy-two weeks of peginterferon-␣2b (1.0 g/kg/week) and ribavirin (800 mg/day) achieved impressive response rates (when compared with those of a historical control) in a small group of slow responders to therapy. 5 In a subgroup analysis from a German multicenter trial, 8 slow responders to peginterferon-␣2a (180 g/week) and ribavirin (800 mg/day) showed statistically superior rates of SVR when treated for 72 weeks compared with 48 weeks. Similarly, in a multicenter trial from Spain using peginterferon-␣2a (180 g/week) and ribavirin (800 mg/day), slow responders benefited from 72 weeks of treatment relative to 48 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-two weeks of peginterferon-␣2b (1.0 g/kg/week) and ribavirin (800 mg/day) achieved impressive response rates (when compared with those of a historical control) in a small group of slow responders to therapy. 5 In a subgroup analysis from a German multicenter trial, 8 slow responders to peginterferon-␣2a (180 g/week) and ribavirin (800 mg/day) showed statistically superior rates of SVR when treated for 72 weeks compared with 48 weeks. Similarly, in a multicenter trial from Spain using peginterferon-␣2a (180 g/week) and ribavirin (800 mg/day), slow responders benefited from 72 weeks of treatment relative to 48 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Although treatment for genotype 1-infected patients is typically given for 48 weeks, there has been interest in extending therapy duration, particularly in slow-responders. 5 Patients treated with peginterferon and ribavirin who do not achieve a 12-week early virologic response (defined by an undetectable serum HCV RNA level or Ͼ2-log decrease relative to a pretreatment RNA level) have only a 3% or lower chance of achieving an SVR. 6,7 However, there is an important dichotomy in response rate between patients who, after 12 weeks of therapy, attain undetectable serum viral RNA versus patients who achieve at least a 2-log decrement in baseline HCV RNA yet still have detectable viremia.…”
mentioning
confidence: 99%
“…HCV RNA analyses were performed at a central laboratory using quantitative reverse transcriptase polymerase chain reaction (COBAS Taqman, Roche) assay with a lower limit of quantitation of 30 IU/mL. HCV RNA levels were evaluated at screening, baseline, and treatment weeks 4,8,12,24,48, and 72 (group B) and at week 24 followup. Trugene HCV Genotyping (Bayer HealthCare LLC, Tarrytown, NY) was used to determine HCV genotype.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Several studies adopting this approach have shown that extending therapy to 72 weeks may increase SVR rates in selected G1 patients. [6][7][8][9][10][11] However, the on-treatment virologic criteria used to select patients for extended therapy vary across studies. Accurately defining which G1 patients will benefit from extended treatment is important, because prolonged treatment is associated with increased adverse events and higher costs.…”
mentioning
confidence: 99%
“…Investigators from Spain and Israel were the first to report successful treatment extension to 72 wk for slow responders to peginterferon and ribavirin [27] . Slow responders were defined as those patients with at least a 2 log 10 decline in HCV RNA from baseline, yet detectable viremia at 12 wk after receipt of 1.0 mcg of peginterferon alpha-2b weekly and 800 mg ribavirin daily.…”
Section: Extended Duration Therapy With Pegylated Interferonmentioning
confidence: 99%